Species-specific and landscape carbon storage analysis of mangrove forest in Segara Anakan Lagoon, Cilacap, Central Java, Indonesia - ENDANG HILMI; HENDRAYANA .HENDRAYANA; SESILIA RANI SAMUDRA; NABELA FIKRIYYA; TEUKU JUNAIDI; TRI NUR CAHYO; NAFSHA ATIKA PUTRI; AFIDA NADZIROTUL UMMAH (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Hilmi E, Hendrayana, Samudra SR, Fikriyya N, Junaidi T, Cahyo TN, Putri NA, Ummah AN. 2024. Species-specific and landscape carbon storage analysis of mangrove forest in Segara Anakan Lagoon, Cilacap, Central Java, Indonesia. Biodiversitas 25: 2748-2755. Mangrove forests are one of the world's largest carbon pools. However, each mangrove species has a different capacity to sequester and store carbon in its biomass. Therefore, at the landscape scale, there are also differences in carbon storage and percent carbon between habitat sites influenced by dominant species and stand density due to differences in environmental conditions. This study aims to analyze each mangrove species' percent carbon and carbon storage and develop a mangrove landscape in Segara Anakan Lagoon, Cilacap District, Central Java Province, Indonesia. This study used destructive methods to collect mangrove samples. The percentage of carbon of each species was analyzed using a formulation of volatile and ash values, while carbon stock for each species was estimated using allometric equations. Landscape analysis of carbon stocks was based on mangrove stand density. The results showed that the carbon percentage of mangrove species averaged between 42.48-53.34% with Rhizophora spp. (R. apiculata, R. mucronata and R. stylosa) and Bruguiera gymnorrhiza having the highest carbon percentage of 47.1-55.6%, followed by Sonneratia spp. and Avicennia with 43.0-48.6%, Ceriops spp., Aegiceras spp., Heritiera littoralis and Xylocarpus spp. with 43.0-48.2%, and Nypa fruticans had the lowest carbon percentage with 39.1-41.0%. At the landscape scale, Segara Anakan had mangrove biomass between 34.83-786.61 tons/ha with carbon stock between 7.85-186.09 tons C/ha. Based on percent carbon, the mangrove landscape in Segara Anakan was dominated by B. gymnorrhiza, R. apiculata, R. stylosa, Ceriops tagal, and R. mucronata. Avicennia marina, Aegiceras corniculatum, N. fruticans, R. apiculata, and Sonneratia alba dominated mangrove landscapes based on carbon storage. The results of this study indicate that carbon storage in mangrove ecosystems is important to support carbon conservation because it has a high percentage of carbon and large carbon storage.